The Effect of Sit Up Exercises on Abdominal Circumference Reduction of UPRI Sports Coaching Education Students - Muhammad Arkanul Arba'; Iin Pratiwi (Universitas Pejuang Republik Indonesia, 2026)
Background: Abdominal circumference is one of the key anthropometric indicators of central obesity and health risk in young adults, including university students. Sedentary habits among sports coaching students who lack structured exercise programs contribute to increased abdominal fat accumulation. Objectives: This study aims to analyze the effect of sit-up exercise on the reduction of abdominal circumference in students of the Sports Coaching Education Program at Universitas Pejuang Republik Indonesia (UPRI) Makassar. Methods: A pre-experimental design with one-group pretest-posttest approach was applied to 30 male students selected through purposive sampling. The sit-up training program was conducted for 8 weeks, 3 sessions per week, with progressive frequency from 3 sets of 15 repetitions increasing to 3 sets of 25 repetitions. Abdominal circumference was measured using a non-elastic anthropometric tape at the level of the navel. Data were analyzed using paired t-test with a significance level of α = 0.05. Results: The mean abdominal circumference before the intervention was 86.74 ± 6.32 cm, which decreased to 83.12 ± 5.87 cm after the 8-week program, representing a reduction of 3.62 cm (p = 0.000 < 0.05). Conclusions: Sit-up exercise performed systematically and progressively for 8 weeks is effective in significantly reducing abdominal circumference in Sports Coaching Education students at UPRI Makassar.